SUMOylation and related post-translational modifications in natural killer cell anti-cancer responses - Molfetta, Rosa; Petillo, Sara; Cippitelli, Marco; Paolini, Rossella (Frontiers in Cell and Developmental Biology, 2023)
SUMOylation is a reversible modification that involves the covalent attachment of small ubiquitin-like modifier (SUMO) to target proteins, leading to changes in their localization, function, stability, and interactor profile. SUMOylation and additional related post-translational modifications have emerged as important modulators of various biological processes, including regulation of genomic stability and immune responses. Natural killer (NK) cells are innate immune cells that play a critical role in host defense against viral infections and tumors. NK cells can recognize and kill infected or transformed cells without prior sensitization, and their activity is tightly regulated by a balance of activating and inhibitory receptors. Expression of NK cell receptors as well as of their specific ligands on target cells is finely regulated during malignant transformation through the integration of different mechanisms including ubiquitin- and ubiquitin-like post-translational modifications. Our review summarizes the role of SUMOylation and other related pathways in the biology of NK cells with a special emphasis on the regulation of their response against cancer. The development of novel selective inhibitors as useful tools to potentiate NK-cell mediated killing of tumor cells is also briefly discussed.